The effect of potato rugose on the yield of some potato varieties - Pohjakallio, Onni; Karhuvaara, Laura; Antila, Simo (Agricultural and Food Science, 1961)
The virus disease occurring in the potato varieties Harbinger, Aquila, and King George V was probably the potato rugose caused by potato virus Y (Solanum virus 2). In the variety Harbinger, the degree of strength of the virus disease probably varied as a result of the appearance of different races of potato virus Y. The type of the virus disease did not change from one vegetative generation of the potato to another. In the potato varieties Aquila and King George V, only the severe type of the disease was observed. The severe type of the virus disease reduced the tuber yield of all the potato varieties investigated to a level of 5 to 6 %, and the slight type occurring in the variety Harbinger to an average of 27 % of the normal. The virus infection appeared more frequently in Harbinger than in the variety Aquila. In the summer, when the infection of the potato plant took place, the virus disease reduced its productivity only relatively little. In the following vegetative generation of the diseased potato plants, the degree of their degeneration conclusively displayed itself. Following this, the wakening of the virus diseased plants did not progress further from one vegetative generation to the next.